Toward a K-20 Student Record Data System for California. - Vernez, Georges (RAND Corp., 2008)
To improve the progression of students through the educational system and to improve education quality, California needs a robust data system that can track an individual student?s progress from kindergarten to college and beyond. Such a data system, commonly called a student unit record (SUR), would contain an individual electronic record of every student enrolled in an educational institution. Currently, 18 states can track individual students from kindergarten through postsecondary education, but California is not one of them. The authors of this report document the state of the various stu.